DIY furniture 2 : a step-by-step guide - Stuart, Christopher (Laurence King Publishing, 2014)
Featuring 30 new designs by leading designer-makers from around the world, DIY Furniture 2 builds on the international success of the previous title, showing you step-by-step how to make unique designer furniture. Including both conceptual objects and modern designs, the book showcases innovative processes using readily available materials commonly found at the local hardware store. Each project features diagrams with short, easy-to-follow instructions on how to build the piece. The projects range from novice to experienced, allowing the reader to start where they are comfortable and work towards more difficult projects as they gain knowledge, familiarity with tools, and confidence.